The effect of dorsal dartos flaps on complication rates in hypospadias repair: A randomised prospective study. Issue 1 (February 2015) - Thomas, David Terence; Karadeniz Cerit, Kivilcim; Yener, Sevim; Kandirici, Aliye; Dagli, Tolga E.; Tugtepe, Halil
Summary Aim This study prospectively analysed the effect of using a dartos flap on the complication rates of TIPU (tubularised incised plate urethroplasty) in hypospadias repair. Material and methods Patients having TIPU repair for hypospadias at our university hospital between January 2010 and August 2013 were prospectively divided into two groups. Group 1 had TIPU repair with dorsal dartos flap, whereas group 2 had flapless repair. At the end of the follow-up period (mean 23.3 m, median 20.2), complication rates were compared between two groups. Results There were 107 patients in each group. The overall complication rate was 9.3%. The complication rates were 12.1% in group 1 (6 glans dehiscence and 7 fistula) and 6.5% in group 2 (2 glans dehiscence and 5 fistula). The differences between complication rates and fistula were statistically insignificant (p = 0.2511 and p = 0.7710, respectively). Conclusion Our prospective and randomised study found that the use of dartos flaps in hypospadias offers no statistically significant advantage over flapless repair for complication rates.